Development of Single Layer Edible Film Composite from Chitosan Nanoparticles-based as Fruit Packaging Materials - Egi Erlangga; Agus Pramono; Endarto Yudo Wardhono (Universitas Sultan Ageng Tirtayasa, 2021)
This experiment was conducted to develop chitosan-based edible films and chitosan nanoparticles with cellulose nanocrystals (CNCs) as stabilizers and fillers. Chitosan nanoparticles were synthesized based on ionic cross-linking with sodium tripolyphosphate and glycerol as plasticizer. The experiment began with making 1% w/v chitosan solution, stirred using a magnetic stirrer at 300 rpm for 24 hours then making CNP-TPP colloid solution, the chitosan solution was heated at 50 oC then added TPP solution with a concentration of 5% as much as 20% by weight. dry chitosan dropwise under constant stirring at 1000 rpm using a magnetic stirrer for five minutes. Making CNP-TPP-CNC-KMnO4 matrix, CNP-TPP colloid solution, added glycerol solution with variations of 5,10 and 15% w/w dry chitosan base and added CNC with variation 1-5% w/w dry chitosan base, stirred at 300 rpm for 30 minutes at room temperature. 8% w/w of dry chitosan base was added with KMnO4 at a temperature of 50 oC under constant stirring at 1000 rpm for five minutes. The film solution was poured into a petri dish and then heated using an oven at 62 oC for 12 hours. Various properties were characterized, mechanical properties and functional group characterization. The experimental results determined the optimum results of the film tensile strength test at 5% CNC and 10% glycerol variations. The tensile strength of the composite film reached a maximum value of 464.1 Mpa on a chitosan-based film and 266.3 MPa on a nano chitosan-based film. The addition of active agent KMnO4 as much as 8% can reduce the value of tensile strength by 46.3%.